EXPERIMENTAL DETERMINATION OF OCTANOL-WATER PARTITION COEFFICIENTS OF FERROCENE DERIVATIVES USING SQUARE WAVE VOLTAMMETRY TECHNIQUES - R. Ahmedi, T. Lanez (University of Eloued جامعة الوادي, 2018)
An electrochemical method based on square wave voltammetry was developed for the measurement of octanol-water partition coefficient, LogP, for ten ferrocene derivatives. Measured LogP values ranged over two orders of magnitude, between 2.18 for 1-ferrocenylethanol and 4.38 for ferrocenyl-2-nitrophenyl. The measured LogP values were compared with those obtained by theoretical calculations developed on the basis of the adaptation of the Rekker method. The correlation coefficient of 0.992 for the comparison of experimental LogP values with those obtained by theoretical calculations indicates an excellent agreement.
Article in Journal of Fundamental and sciences. university of el oued
Keywords: Partition coefficients, log P, ferrocene derivatives, square wave voltammetry